Integrasi Data TLS dan UAV Untuk Pemodelan 3D Gua Aul di Kabupaten Ciamis - Daffa Fadhillah Akbar; Gusti Ayu Jessy Kartini (Jurnal Serambi Engineering, 2025)
Gua Aul, located in Ciamis Regency, is a cultural heritage site with significant historical and scientific value. To support preservation efforts and digital documentation, this study aims to produce a 3D model of Gua Aul by integrating data from a Terrestrial Laser Scanner (TLS) and an Unmanned Aerial Vehicle (UAV). TLS data was used to map the cave interior with high accuracy and density, while UAV data captured the cave exterior, including the surrounding topographic area. The registration process employed an independent georeferencing method, in which each point cloud was tied to the global coordinate system WGS 84/UTM Zone 49S using GNSS data. The integration of interior and exterior point clouds resulted in a complete 3D model, with geometric validation accuracy showing an overall RMSE of 0.005 m, indicating a very small and acceptable average deviation of the TLS and UAV integration compared to the actual dimensions. This integration result was not significantly different from the actual object size based on a t- distribution statistical test at a 95% confidence level. The resulting 3D modeling is expected to serve as a medium for documentation, education, as well as a foundation for sustainable conservation and management of the cultural site. Thus, the integration of TLS and UAV has proven to be an effective and adaptive approach to supporting the protection of cultural heritage in the future.